Rupture and variable coupling behavior of the Mentawai segment of the Sunda megathrust during the supercycle culmination of 1797 to 1833 - Philibosian, Belle (2015)
We refer to periods of subduction strain accumulation beneath the Mentawai Islands, Sumatra, as “supercycles,” because each culminates in a series of partial ruptures of the megathrust in its final decades. The finale of the previous supercycle comprised two giant earthquakes in 1797 and 1833 and whatever happened in between. This behavior between two great ruptures has implications for how the megathrust will behave between its more recent partial failure, during the Mw 8.4 earthquake of 2007, and subsequent large ruptures. We synthesize previously published coral microatoll records and a large new coral data set to constrain not only these two giant ruptures but also the intervening interseismic megathrust behavior. We present detailed maps of coseismic uplift during the two earthquakes and of interseismic deformation during the periods 1755–1833 and 1950–2000, as well as models of the corresponding slip and coupling on the underlying megathrust. The large magnitudes we derive (Mw 8.6–8.8 for 1797 and Mw 8.8–8.9 for 1833) confirm that the 2007 earthquakes released only a fraction of the moment released during the previous rupture sequence. Whereas megathrust behavior leading up to the 1797 and 2007 earthquakes was similar and comparatively simple, behavior between 1797 and 1833 was markedly different and more complex: several patches of the megathrust became weakly coupled following the 1797 earthquake. We conclude that while major earthquakes generally do not involve rupture of the entire Mentawai segment, they may significantly change the state of coupling on the megathrust for decades to follow, influencing the progression of subsequent ruptures.